Mức độ hiệu quả của hoạt động quản lí hỗ trợ học tập nhằm nâng cao hiệu quả đào tạo sinh viên chính quy: Nghiên cứu tại Trường Đại học Khoa học - Đại học Thái Nguyên - Phí Đình Khương, Phí Đình Khương; Nguyễn Thị Thu Trang, Nguyễn Thị Thu Trang; Trịnh Thanh Tuấn, Trịnh Thanh Tuấn (Tạp chí Giáo dục, 2026)
In the context of higher education promoting digital transformation and focusing on training efficiency, supporting students to improve their learning capacity is an urgent requirement. The article focuses on surveying and analyzing 05 groups of learning support management content for full-time students at the University of Science - Thai Nguyen University through processing with quantitative methods including scale reliability testing, descriptive statistics, T-test, ANOVA, Pearson correlation and multivariate regression. The results show that 05 groups of learning support management content all have high reliability and close relationship. The factors of information technology application and monitoring - feedback have the strongest impact on learning efficiency, contributing to limiting the risk of learning warning. The study not only provides additional empirical evidence but also suggests specific management solutions in subsequent studies, contributing to improving training quality and limiting dropout rates in the current context of Vietnamese higher education.